Fatliquor Development from Hemp Oil to Produce High Quality Natural Finished Leather - Sarwat Jahan Mahboob (Indonesian Journal of Chemistry and Environment, 2022)
Fatliquors are very important in the manufacture of leather. Leather treated with fatliquor become more flexible and softer by the separation of leather fibers in the wet state so that they do not stick too much during drying, also the physical properties, such as tensile strength, softness, tear strength and stability of the leather become influenced simultaneously. The step of fatliquoring is carried out during leather processing operation after tanning. Variety of fatliquors is synthesized so far from various vegetable oils. In this study, for the first time, fat-liquor, named as, “Hempfat” is synthesized from oil extracted from hemp seeds. As hemp oil consists of high amount of omega-6, omega-3 fatty acids possessing antioxidant activities, so accepted as beneficial to health for public, also possess high kinetic stability and increased protective effect during increase or decrease of temperature. On high temperatures, trans-fatty acids are not formed. So the developed fatliquor, “Hempfat” and the leather developed from it were evaluated on physical and chemical grounds, both found to possess the excellent properties of a fatliquor as leather fatliquoring agent in making good quality finished natural leather.